Recurrent retrorectal tailgut cyst mimicking deep pelvic abscess: A diagnostic dilemma - Summi Karn, MBBS; Farhanul Huda, MBBS, MS; Lena Elizabath David, MBBS; Jyoti Sharma, MBBS, MS; Tripti Prajapati, MBBS, MD; Udit Chauhan, MBBS, MD; Sudhir Kumar Singh, MBBS, MS; Somprakas Basu, MBBS, MS, FRCS (Radiology Case Reports, 2022)
Tailgut cysts are congenital anomalies that are rare and arise from incompletely regressed primitive hindgut. These are more commonly found in women and are usually asymptomatic. When symptoms develop, these can present with pain, infection, hemorrhage, difficulty in defecation, and rarely malignant change. We report a middle-aged married woman who presented with deep-seated perineal pain for a couple of months, which increased during defecation and sexual intercourse. Although abdominal examination was unremarkable barring deep tenderness in the hypogastrium, rectal and vaginal examinations suggested a tender pelvic swelling. An abdominal ultrasonographic examination diagnosed a cystic swelling in the pelvis extending until the Levator ani muscles. Considering her symptoms, a pelvic abscess was diagnosed and transvaginal drainage was done. Due to persistence of symptoms and recurrence after a month, she was further investigated and was diagnosed to have a presacral benign cystic tumor based on CT and MRI scans of the pelvis. The lesion was completely excised through a combined abdomino-perineal approach and histopathological report suggested a benign tailgut cyst. That a cystic presacral swelling with features of inflammation can be confused with a deep pelvic abscess is hereby highlighted in this report. An MRI scan is diagnostic of these lesions. Failure to differentiate it from a pelvic abscess may result in drainage, which may be of concern if the lesion is malignant.